(3JdNjU GdahGFO TQM GdbUjOI GdQGFjIs - (3Ydj Hf YKeGf Hf eMeO Hf CMeO Hf GdMSjf GdeYQha HGHf GdbGUM GdYPQi GdHZOGOjs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3bhdg GdMeO ddg ehJ GdMeO ddg gh GdKfGA Ydi Gddg hbhdg ehUdoG OGFekG CHOkG dG jfbWY dG aj GdOfjG hdGaj GdCNQI s
(3BNQgG (B:s
(3hdcf CQGO GdfGXe QMeg Gddg gfG hGdCUGd LeY CUhd Je gPG GdcJGH HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs